Spritualization Of New Media With Islamic Values Study Of Sa'id Nursi's Thinking In The Media Field - Adeni Adeni; H. M. Alfandi (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2023)
This article aims to study the contribution of Badi’uzzaman Said Nursi in the Islamic media field. His thoughts can be considered a solution to social problems caused by globalization. This study uses a qualitative method based on literature studies in which the primary data source is Risale-I Nur, the monumental work of Said Nursi. The results show that Said Nursi displayed "media terms" in the basic sense of media as a liaison and an intermediary between one society and another as seen from the terms of airplane, railway, radio, telegraph, telephone, and newspaper. Second, Nursi views media as communication tools, but rather, he discussed media in terms of ma'nai harfi, in which media and all its usage forms must be connected to Allah. Nursi reconstructed the meaning system (semiology) of media content that is mostly dominated by merely individual desires and social contexts, avoiding moral values. Third, Nursi's thought can be applied in the context of recent new media advancement. It can be used for promoting peace and the beautifulness of the Quran's content to the whole globe. Therefore, Nursi's thought can be considered a reference for solving moral media problems facing society.